1985
DOI: 10.1148/radiology.156.3.4023243
|View full text |Cite
|
Sign up to set email alerts
|

Pectus excavatum in children: pulmonary scintigraphy before and after corrective surgery.

Abstract: Regional distribution of pulmonary function was evaluated preoperatively and postoperatively with xenon-133 perfusion and ventilation scintigraphy in 17 patients with pectus excavatum. Ventilatory preoperative studies were abnormal in 12 of 17 patients, resolving in seven of 12 postoperatively. Perfusion scans were abnormal in ten of 17 patients preoperatively; six of ten showed improvement postoperatively. Ventilation-perfusion ratios were abnormal in ten of 17 patients, normalizing postoperatively in six of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The findings are consistent with previous reports [17][18][19]. Blickman et al [20] reported that impairment of either ventilation or perfusion or both are observed primarily in the left lower lung, and that surgery improves these abnormalities in virtually all patients with PE. Thus, we speculate that moving the mediastinum to its correct position by surgical repair may contribute in part to improved pulmonary perfusion followed by relief of symptoms and increased stroke volume.…”
Section: Discussionsupporting
confidence: 93%
“…The findings are consistent with previous reports [17][18][19]. Blickman et al [20] reported that impairment of either ventilation or perfusion or both are observed primarily in the left lower lung, and that surgery improves these abnormalities in virtually all patients with PE. Thus, we speculate that moving the mediastinum to its correct position by surgical repair may contribute in part to improved pulmonary perfusion followed by relief of symptoms and increased stroke volume.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 313 pectus excavatum patients were assessed in the meta-analysis. Four studies did not report a pectus severity index [13,34,36,39], whereas the remaining studies used various techniques for estimating a pectus severity index [6][7][8]12,37,40,41]. Therefore, the relationship between pectus severity and the average ES for each study could not be examined in the present study.…”
Section: Study Characteristicsmentioning
confidence: 96%
“…Furthermore, reference lists from original and review articles were reviewed to identify any studies that had not been previously identified from the computerized searches. As a result, 19 studies met all of the inclusion criteria [6][7][8]11,13,[34][35][36][37][38][39][40][41][42][43][44][45][46]. The studies by Gyllensward et al [44,45] and Borowitz et al [46] did not provide sufficient statistical information to estimate ESs for pulmonary function indices for patients who had surgical repair.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations